(untitled) (MUST JOURNAL OF RESEARCH AND DEVELOPMENT, 2025)
The utilization of renewable energy hybrid systems has emerged as a viable solution for addressing electricity challenges in developing regions. This study assesses the electricity demand of the Kitai Prisons Complex in Tanzania to evaluate the potential integration of a renewable energy hybrid system. The research employs load classification, daily load profiling, and energy forecasting to analyze the electricity consumption patterns within the complex. Detailed assessments of current demand and future projections were conducted to ensure compatibility with Renewable energy hybrid systems. Key findings reveal distinct load categories, including residential, administrative, and industrial operations, each with unique demand characteristics. Daily load profiles highlight significant peaks during morning and evening hours, necessitating optimized storage and generation strategies. Energy forecasting models predict increasing demand due to planned infrastructure expansions. The study concludes by recommending a hybrid energy system tailored to meet current and future electricity needs while enhancing energy reliability and sustainability. These findings provide critical insights for implementing renewable energy solutions in institutional facilities across Tanzania and similar contexts in East Africa. HOMER Pro program is developed and implemented to obtain the load profiles of different customer groups.